1991
DOI: 10.1063/1.859596
|View full text |Cite
|
Sign up to set email alerts
|

TEXT tokamak edge turbulence modeling

Abstract: Experimental results on the Texas Experimental Tokamak (TEXT) [Nucl. Technol./Fusion 1, 479 (1982)] and the Advanced Toroidal Facility (ATF) torsatron [Fusion Technol. 10, 179 (1986)] indicate that electrostatic fluctuations can explain the edge transport of particles and perhaps energy. Certain mechanisms for drive (radiation and ionization, as well as density and temperature gradients) and stabilization (velocity shear) are suggested by these results. The experimental fluctuation levels and turbulence charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Ionization-driven drift wave instabilities have been considered as potential candidates to explain inward-directed particle fluxes [34]. Though ionization in the H-1 occurs in the inner plasma regions [22], introducing a potential drive for the ionization drift waves, there are several counter arguments.…”
Section: Discussionmentioning
confidence: 99%
“…Ionization-driven drift wave instabilities have been considered as potential candidates to explain inward-directed particle fluxes [34]. Though ionization in the H-1 occurs in the inner plasma regions [22], introducing a potential drive for the ionization drift waves, there are several counter arguments.…”
Section: Discussionmentioning
confidence: 99%
“…38 The question of the role of low-q surfaces in confinement has a long history. [39][40][41][42][43] Low-q surfaces have in the past been associated with microtearing modes, magnetic islands of unexplained origin, etc., all with the aim of providing a physical basis for the notion of profile consistency. Previous work 44 has also suggested that spikes or humps in the fluctuation intensity profile may sit at low-q resonances, and that these localized intensity gradients may drive sheared poloidal flow via the Reynolds stress.…”
Section: ͑49͒mentioning
confidence: 99%
“…There is experimental evidence showing that the induced turbulent transpon can account for most of the particle transport in the edge región of the plasma in tokamaks and stellarators [1,2]. However, although our understanding of the plasma turbulence has been improved during the last few years, the dominant free energy source responsible for the turbulence (Vn, VT, VZ,...) has not been identified yet [3,4].…”
mentioning
confidence: 99%
“…In the present experiments, plasmas have been obtained using electron cyclotron heating (ECH). Discharges with PECH = 200-400 kW, & J (4)(5)(6) x 10" ~m -~, stored energy SE = 1-2 kJ and magnetic field B = 1 T have been studied. Plasma edge turbulence has been characterized by means of Langmuir probes using the experimental methods described previously [2, 61.…”
mentioning
confidence: 99%